Favorable response to second-line atezolizumab and bevacizumab following progression on nivolumab in advanced hepatocellular carcinoma: A case report demonstrating that anti-VEGF therapy overcomes resistance to checkpoint inhibition. Issue 25 (25th June 2021) - Swed, Brandon; Ryan, Kara; Gandarilla, Omar; Shah, Manish A.; Brar, Gagandeep
Abstract: Rationale: Advanced hepatocellular carcinoma (HCC) remains a deadly disease in part due to decades of limited therapeutic options. With recent advances in our understanding of the tumor biology, several promising treatment strategies involving targeted and immunotherapies have emerged. However, enhancing their modest efficacy in HCC and other gastrointestinal malignancies is essential to improving survival. Patient concerns: A man in his late 50s with a history of type 2 diabetes mellitus and morbid obesity initially presented with progressive abdominal pain and anorexia prompting an abdominal computed tomography scan that revealed a large solitary liver mass with extensive local involvement. Diagnoses: Although there were features consistent with a primary gastric tumor on subsequent endoscopic evaluation leading to early diagnostic uncertainty, his clinical picture, including a dominant liver mass, immunohistochemical staining profile, and significantly elevated alpha fetoprotein ultimately favored HCC. Interventions: The patient received palliative systemic therapy with infusional fluorouracil for a presumed gastric primary, however restaging scans after 3 cycles demonstrated disease progression. The consensus from a multidisciplinary discussion was that his pathology was more consistent with primary HCC. He was subsequently started on nivolumab with a partial response, although after 5 months, he progressed prompting initiation of second-line atezolizumab and bevacizumab with a favorable response. Outcomes: The addition of atezolizumab and bevacizumab led to a sustained biochemical and radiographic response that appeared to overcome the resistance to nivolumab monotherapy. Aside from several mild immune-related adverse effects, his quality of life has greatly improved and he has tolerated treatment well to date. Lessons: Our findings suggest that vascular endothelial growth factor inhibition can overcome resistance to checkpoint inhibition in advanced HCC by resulting in a unique synergy that has never before been described in patients. The biological rationale for this response is likely attributable to the immunomodulatory effects of antiangiogenic agents, promoting an immunostimulatory microenvironment that can be exploited by immune checkpoint inhibitors for more effective antitumor activity. Given the considerable benefit patients may derive following progression on first-line treatment, it is important to consider this strategic combination of therapies which can ultimately lead to improved patient outcomes.